Size-related cytotoxicological aspects of polyvinylpyrrolidone-capped platinum nanoparticles. (July 2017) - Buchtelova, Hana; Dostalova, Simona; Michalek, Petr; Krizkova, Sona; Strmiska, Vladislav; Kopel, Pavel; Hynek, David; Richtera, Lukas; Ridoskova, Andrea; Adam, Pavlina; Kynicky, Jindrich; Brtnicky, Martin; et al.
Abstract: The nanotechnological concept is based on size-dependent properties of particles in the 1–100 nm range. Nevertheless, the connection between their size and effect is still not clear. Thus, we focused on reductive colloidal synthesis, characterization and biological testing of Pt nanoparticles (PtNPs) capped with biocompatible polymer polyvinylpyrrolidone (PVP). Synthesized PtNPs were of 3 different primary sizes (approx. ∼10; ∼14 and > 20 nm) and demonstrated exceptional haemocompatibility. In vitro treatment of three different types of malignant cells (prostate – LNCaP, breast – MDA-MB-231 and neuroblastoma – GI-ME-N) revealed that even marginal differences in PtNPs diameter resulted in changes in their cytotoxicity. The highest cytotoxicity was observed using the smallest PtNPs-10, where 24IC50 was lower (3.1–6.2 μg/mL) than for cisplatin (8.1–19.8 μg/mL). In contrast to MDA-MB-231 and LNCaP cells, in GI-ME-N cells PtNPs caused noticeable changes in their cellular structure without influencing their viability. Post-exposure analyses revealed that PtNPs-29 and PtNPs-40 were capable of forming considerably higher amount of reactive oxygen species with consequent stimulation of expression of metallothionein (MT1/2 and MT3), at both mRNA and protein level. Overall, our pilot study demonstrates that in the nanoscaled world even the smallest differences can have crucial biological effect. Highlights: Three different primary sizes of Pt nanoparticles were synthesized. These were tested on prostate, breast and neuroblastoma cancer cell lines. The highest cytotoxicity was identified for the smallest PtNPs. Changes of ROS and expression of metallothioneins were also evidenced.